Efficient in situ N-heterocyclic carbene palladium(ii) generated from Pd(OAc)2 catalysts for carbonylative Suzuki coupling reactions of arylboronic acids with 2-bromopyridine under inert conditions leading to unsymmetrical arylpyridine ketones: synthesis, characterization and cytotoxic activities. Issue 70 (5th December 2018) - Touj, Nedra; Al-Ayed, Abdullah S.; Sauthier, Mathieu; Mansour, Lamjed; Harrath, Abdel Halim; Al-Tamimi, Jamil; Özdemir, Ismail; Yaşar, Sedat; Hamdi, Naceur
Abstract : The in situ prepared four component system Pd(OAc)2, 1, 3-dialkylbenzimidazolium halides2a–i and4a–i, K2 CO3 under CO atmosphere catalyses carbonylative cross-coupling reaction of 2-bromopyridine with various boronic acids to yield unsymmetrical arylpyridine ketones. Abstract : N, N -Substituted benzimidazole salts were successfully synthesized and characterized by 1 H-NMR, 13 C 1 H NMR and IR techniques, which support the proposed structures. Catalysts generated in situ were efficiently used for the carbonylative cross-coupling reaction of 2 bromopyridine with various boronic acids. The reaction was carried out in THF at 110 °C in the presence of K2 CO3 under inert conditions and yields unsymmetrical arylpyridine ketones. All N, N -substituted benzimidazole salts2a–i and4a–i studied in this work were screened for their cytotoxic activities against human cancer cell lines such us MDA-MB-231, MCF-7 and T47D. The N, N -substituted benzimidazoles2e and2f exhibited the most cytotoxic effect with promising cytotoxic activity with IC50 values of 4.45 μg mL −1 against MDA-MB-231 and 4.85 μg mL −1 against MCF7 respectively.